The Authenticity of Assessment Used In Reading Class At The Third Semester Of English Education Program In Universitas Pekalongan Academic Year 2016/2017 - Hapsari, Anggi Sinta; , Mauly Halwat Hikmat, Ph. D; , Dr. Anam Sutopo, M.Hum (2017)
This research was a case study of the authenticity of ssment used in reading class at the third semester of English education program in Universitas Pekalongan academic year 2016/2017. The objectives of this study were (1) to describe the types of assessments used in reading class at the third semester in Universitas Pekalongan, (2) to describe the most frequently assessment used in reading class at the third semester in Universitas Pekalongan, (3) to know the enticity of the assessment used by the lecturer in reading class, and (4) to describe the problems faced by lecturer in applying authentic assessments in reading class at the third semester in Universitas Pekalongan. The type of the research was qualitative research with case study. The object of the study was the authenticity of assessment which used in III-A and III-B classes of reading for academic purposes at the third semester in Universitas Pekalongan academic year 2016/2017. The subject of the study was an English Lecturer who taught Reading for Academic Purposes at the third semester in Universitas Pekalongan academic year 2016/2017. The data sources used in this study were informant, document, and event. The techniques for collecting data were observation, interview, and documentation. The data validity used in this study was data triangulation and iter-rater reliability. Then the researcher used Miles and Hubberman's Model (1994) to analyze the data. The result of this study showed that the lecturer used two types of assessment, namely performance and teacher observation in formative and summative assessment. The performance is in the form of oral presentation and the teacher observation is in the form of anecdotal records.The performance combined with teacher observation was frequently used assessment by lecturer in assessing students' outcome in reading for academic purposes class since they are the only assessment used by the lecturer. In addition, performance and teacher observation in the formative and summative assessment of reading for academic purposes had high level of the authenticity. Then, the problem in applying authentic assessment in reading class was the lecturer had difficulty in administrating authentic assessment because he scored the students one by one by writing every student's reading competence including their cognitive, affective, and psychomotoric. Keyword: Authenticity; Reading Assessment, Authentic Assessment.